Primary Myxoid Liposarcoma of the Ovary in a Postpartum Female: A Case Report and Review of Literature. (May 2015) - Liang, Sharon X.; Howitt, Brooke; Blitz, Matthew J.; Bhuiya, Tamfiqul; Thamasebi, Farnaz; Sternchos, Jason; Shih, Karin
Abstract : A 36-year-old gravida 4, para 2 African-American woman, presented at three months postpartum with a right ovarian mass identified on a lumbar spine MRI as part of a neurology workup for persistent lower back pain. A follow-up pelvic ultrasound noted a 7.0×6.1×3.8 cm septated mixed cystic and solid mass. Exploratory laparoscopy and right ovarian cystectomy yielded a final pathologic diagnosis of intermediate grade myxoid liposarcoma, confirmed with DDIT3 gene rearrangement studies.